The rediscovery of Ipomoea macedoi (Convolvulaceae) - Marinho, Antoniela Morais; Delgado-Júnior, Geadelande Carolino; Buril, Maria Teresa (Phytotaxa, 2017)
A new population of Ipomoea macedoi, a critically endangered species from Brazil, was found in Chapada do Apodi (Rio Grande do Norte State). The species is recognized by its large, distinctly cordate outer sepals. A detailed description, comments on its distribution and conservation, a taxonomic comparison, photographs and a line drawing are provided.